PENGARUH DIMENSI PREFERENSI WISATAWAN NUSANTARA TERHADAP KEPUTUSAN BERKUNJUNG KE DAYA TARIK WISATA BUNTU BURAKE KAB. TANA TORAJA - Yosal, Noviesya; Dewi, LGLK.; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022), 2023)
Tourism becomes leading sector in obtaining foreign exchange but COVID-19 pandemic affected tourism sectors. The government adapt and depend on domestic tourist. As one of tourist destination in Kabupaten Tana Toraja, Buntu Burake tourist destination being closed for 2 years due to COVID-19 pandemic set them to keep improving to evolve. Knowledge related to tourist preference are useful towards tourism product suitable with tourist expectation so that tourism business especially on tourist destination could adapt with tourist needs. This study aim to know the characteristic of domestic tourist and how the domestic tourist preference when they are visiting Buntu Burake tourist destination. Sampling technique done by purposive sampling by collecting data from sharing 100 questionnaires directly and online, observasion, interview, literature studies, and documentation. Data Analysis Technique in this study use SmartPLS (v. 3.3.9) by following step from outer model, inner model, and assumption test.  The results of this study state that attraction, transportation, and infrastructure are significantly influence towards domestic tourist intention to visit Buntu Burake tourist destination while facilities and hospitality are not significantly influence towards domestic tourist intention to visit Buntu Burake tourist destination.